Analysis of the Impact of the Implementation of the Interest System in KUR on the Income and Quality of Life of MSMEs in Yogyakarta A Sharia Economic Perspective - Hariyatin, Cindy Putri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study analyzes the impact of interest-based Kredit Usaha Rakyat (KUR) on the income and quality of life of MSMEs in Yogyakarta from an Islamic economic perspective. Using a quantitative approach with survey techniques, data were collected via questionnaires and analyzed using linear regression. Findings indicate that while KUR provides easier capital access, interest burdens reduce income, business sustainability, and MSME quality of life. From an Islamic perspective, interest-based systems are non-compliant due to riba elements. This study recommends Sharia-based financing schemes for more sustainable MSME support.